Analysis of expressed sequence tags from Prunus mume flower and fruit and development of simple sequence repeat markers - Gao Zhihong; Wang Chen; Song Changnian; Shangguan Lingfei; Li Xiaoying; Yu Huaping; Fang Jinggui (BMC Genetics, 2010)
Abstract Background Expressed Sequence Tag (EST) has been a cost-effective tool in molecular biology and represents an abundant valuable resource for genome annotation, gene expression, and comparative genomics in plants. Results In this study, we constructed a cDNA library of Prunus mume flower and fruit, sequenced 10,123 clones of the library, and obtained 8,656 expressed sequence tag (EST) sequences with high quality. The ESTs were assembled into 4,473 unigenes composed of 1,492 contigs and 2,981 singletons and that have been deposited in NCBI (accession IDs: GW868575 - GW873047), among which 1,294 unique ESTs were with known or putative functions. Furthermore, we found 1,233 putative simple sequence repeats (SSRs) in the P. mume unigene dataset. We randomly tested 42 pairs of PCR primers flanking potential SSRs, and 14 pairs were identified as true-to-type SSR loci and could amplify polymorphic bands from 20 individual plants of P. mume. We further used the 14 EST-SSR primer pairs to test the transferability on peach and plum. The result showed that nearly 89% of the primer pairs produced target PCR bands in the two species. A high level of marker polymorphism was observed in the plum species (65%) and low in the peach (46%), and the clustering analysis of the three species indicated that these SSR markers were useful in the evaluation of genetic relationships and diversity between and within the Prunus species. Conclusions We have constructed the first cDNA library of P. mume flower and fruit, and our data provide sets of molecular biology resources for P. mume and other Prunus species. These resources will be useful for further study such as genome annotation, new gene discovery, gene functional analysis, molecular breeding, evolution and comparative genomics between Prunus species.